2022
DOI: 10.1038/s41598-022-22462-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid cancer and cardiovascular disease risk: a nationwide observation study

Abstract: Treatment with levothyroxine and radioiodine contribute alternative cardiovascular function in adults with thyroid cancer. The risks of long-term cardiovascular conditions among thyroid cancer patients is unknown. This study aimed to compare the incidence of coronary heart disease (CHD), ischemic stroke (IS), and atrial fibrillation (AF) among adults with thyroid cancer with that of the general population, especially when stratified by age (< 65 and ≥ 65 years old). This observational cohort study enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A total of 146 studies were ultimately included in our meta‐analysis 9,24–167 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 146 studies were ultimately included in our meta‐analysis 9,24–167 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In Taiwan, cardiovascular disease is the third leading cause of mortality in thyroid cancer patients [23]. We recently demonstrated that, compared to the general population, thyroid cancer survivors have a substantial risk of coronary heart disease [24]. Some experts have proposed that surgical management of elderly patients with thyroid cancer should be tempered when high-risk findings (aggressive tumor type and metastasis) are absent, especially for those who have comorbid illnesses [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, 4932 new cases were diagnosed in 2020, making it the fourth most common cancer in females and 30th in males. A large population-based study indicates a rising overall incidence of thyroid cancer in Taiwan over a 25-year period, across all age groups and major tumor types [ 2 ]. Globally, the incidence rate of thyroid cancer in women is 3 times higher than in men [ 1 ], a trend also observed in Taiwan.…”
mentioning
confidence: 99%